2014
DOI: 10.1245/s10434-014-4225-1
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant Modified (m) FOLFIRINOX for Locally Advanced Unresectable (LAPC) and Borderline Resectable (BRPC) Adenocarcinoma of the Pancreas

Abstract: Background For patients with metastatic pancreatic cancer, FOLFIRINOX (fluorouracil [5-FU], leucovorin [LV], irinotecan [IRI], and oxaliplatin) has shown improved survival rates compared with gemcitabine but with significant toxicity, particularly in patients with a high tumor burden. Because of reported response rates exceeding 30 %, the authors began to use a modified (m) FOLFIRINOX regimen for patients with advanced nonmetastatic disease aimed at downstaging for resection. This report describes their experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
164
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(179 citation statements)
references
References 16 publications
(16 reference statements)
14
164
1
Order By: Relevance
“…In addition, Faris et al evaluated the FOLFIRINOX regimen for the treatment of LURPC and found an RR of 27%, as well as favorable treatment outcomes (median disease-free survival: 11.3 months); however, the median survival time was not reported (3). Moreover, Nanda and Blazer et al also reported favorable outcomes when they compared FOLFIRINOX with CRT for the treatment of LURPC, with median survival times of 18.6 and 12.2 months, respectively (16,17). During the present study, the RR was 71%, and although the median survival time was not calculated, the mean survival time was 13.3 months.…”
Section: Discussionsupporting
confidence: 43%
“…In addition, Faris et al evaluated the FOLFIRINOX regimen for the treatment of LURPC and found an RR of 27%, as well as favorable treatment outcomes (median disease-free survival: 11.3 months); however, the median survival time was not reported (3). Moreover, Nanda and Blazer et al also reported favorable outcomes when they compared FOLFIRINOX with CRT for the treatment of LURPC, with median survival times of 18.6 and 12.2 months, respectively (16,17). During the present study, the RR was 71%, and although the median survival time was not calculated, the mean survival time was 13.3 months.…”
Section: Discussionsupporting
confidence: 43%
“…Resection was attempted in 72% of cases, including 11 of 25 LAPC cases (44%). R0 resection was obtained in 86.4%, or 19 of 22, with an 18-month median PFS for patients undergoing resection compared with 8 months for patients who did not undergo resection [6]. At Memorial Sloan-Kettering Cancer Center, LAPC patients (101) received FOLFIRINOX followed by CRT.…”
Section: Induction Chemotherapy Followed By Chemoradiationmentioning
confidence: 99%
“…LAPC is treated with combination chemotherapy or combined chemoradiation therapy (CRT). These approaches have not shown any improvement in survival [6,7]. In this review, we highlight the evidence that defines the treatment approach for BRPC and LAPC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FOLFIRINOX, a promising mixture of cytotoxic agents including folinic acid (leucovorin), fluorouracil, irinotecan, and oxaliplatin, has limited use in many patients because of its high systemic toxicity (16,17). Modified FOLFIRINOX regimens have been created to improve tolerability (5,18). Given the ability of the iontophoretic device to deliver drugs locally with minimal systemic exposure, the iontophoretic delivery of FOLFIRINOX Significance Drug delivery to pancreatic tumors is impaired by a unique desmoplastic response and poor tumor vascularization.…”
mentioning
confidence: 99%